TECHNOLOGY AND THE "NORMAL" IN THE CORONAVIRUS ERA - Cristina Gularte Liberato , Carla (Health and Society, 2021)
Pandemic, although devastating in some aspects, is spreading rapidly as is technological growth. In times of social isolation, so much has never been learned through digital platforms, jobs are reinvented at unparalleled speed. Patients are treated in telehealth, a technology that stands out at the moment, a useful tool for initial or follow-up care. Real-time monitoring with GPS, Google platforms, wearable technologies, a range of options still without legislation and correct coverage. Reflecting on your personal and professional life, the Coronavirus, for sure, will divide our existence into before and after, and what was “normal” before, will remain unchanged afterwards? Reflections on technology, management and personal development.